Driver adaptation to information and assistance systems - Stevens, A. (Researcher in transportation); Brusque, Corinne; Krems, Josef (Institution of Engineering and Technology, 2014)
Driver information and assistance systems have emerged as an integral part of modern road vehicles in order to support the driver while driving.